(untitled) (Research, Society and Development, 2021)
The objective of this work was to analyze the impact of the COVID-19 pandemic on the financial management of micro and small companies in the retail sector in Cláudio-MG. An exploratory research was carried out, with a quantitative approach, through a case study of micro and small companies in the retail sector that were part of the campaign “Conscious Trade Against COVID-19”, in Cláudio-MG. The information was collected through a questionnaire using the google forms application. It was identified that the majority of companies were predominantly in the clothing industry and operated in the market for two to five years. Financial management was carried out by the entrepreneurs themselves, most of whom were female, worked in the financial area for one to five years, had completed high school and had no training in the financial area, however, during the pandemic some sought training in the area. Before the pandemic, most of the sample had growing revenues, were able to pay their bills on time and it was not the daily practice of companies to systematically use financial management tools. The most used ones were cash flow control, accounts payable and receivable control, cost control, inventory control and they made sales by credit card. With the crisis caused by the pandemic, revenues decreased and they began to have more difficulty in keeping payments up to date. A part of them had increased costs with personnel, taxes, electricity, among others. They continued to use the same tools used before the pandemic, but more companies started using them. The analysis of the need for working capital, which was little used, started to be used by more companies. Therefore, the main impacts caused by the crisis resulting from the pandemic on most companies were negative, among them are the drop in revenues; the change in the way the company works; the increase in expenses, mainly with personnel, electricity, water and taxes; the dismissal or removal of employees, reduced working hours and suspension of the employment contract; among others. However, some had a positive impact, considering that there was an increase in sales.